1995
DOI: 10.1097/00000542-199505000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol on Calcium sup 2+ Regulation by Malignant Hyperthermia-susceptible Muscle Membranes 

Abstract: In contrast to malignant hyperthermia-triggering inhalation anesthetics, propofol does not stimulate malignant hyperthermia-susceptible or normal ryanodine receptor channel activity, even at > 100 times clinical concentrations. Effects on dihydropyridine receptor and Ca(2+)-ATPase function, however, are similar to the effects of inhalation anesthestics and require much lower concentrations of propofol. These findings, demonstrating that propofol does not activate ryanodine receptor Ca2+ channels, suggest a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
2
8
0
2
Order By: Relevance
“…It has been reported that propofol does not trigger MH and is thus a safe anaesthetic for MH patients (Fruen et al 1995;Barhoumi et al 2007;Migita et al 2007). In this case, hyperthermia developed again following propofol administration.…”
Section: Case Descriptionmentioning
confidence: 63%
“…It has been reported that propofol does not trigger MH and is thus a safe anaesthetic for MH patients (Fruen et al 1995;Barhoumi et al 2007;Migita et al 2007). In this case, hyperthermia developed again following propofol administration.…”
Section: Case Descriptionmentioning
confidence: 63%
“…Musküler distrofili hastalarda, propofol, remifentanil gibi intravenöz anestezik ajanlar yaygın olarak kullanılmaktadır (17,18) . Propofol infüzyonunun riyanodin-Ca reseptörlerini aktive ederek malign hipertermi riskinde güvenli bir alternatif seçenek olduğu gösterilmiştir (19) . Olgumuzda, anestezi yöntemi olarak total intravenöz anestezi (TİVA) uygulaması için propofol infüzyonunu ve remifentanil infüzyonunu yeğledik.…”
Section: Discussionunclassified
“…propofolün 100 katından daha fazla klinik konsantrasyonlarında bile malign hipertermiye duyarlı riyanodin reseptörlerinin kanal aktivitesini stimüle etmediğini bildirmiştir. 9 Malign hipertermiye yatkınlığı olan olgularda inhalasyon ajanları yerine propofol kullanımının güvenli olduğunu, LGMD'li olgularda anestezi indüksiyonu ve idamesinde propofolün başarıyla kullanıldığını destekleyen yayınlar bulunmaktadır. 6,7,10 Biz konjenital kalp cerrahisi geçiren çocuk olgumuzda negatif inotropik özelliği bulunan propofolü hipotansiyon yapma riski nedeniyle tercih etmedik.…”
Section: Discussionunclassified